Performance and emission analysis of engine using Naviculla Sp. Algae oil methyl ester with La2O3 nanoparticles. (2020) - Arunprasad, J.; Elango, T.
Abstract: Recently, suppliers have been completely investing in making an alternative fuel to exchange the exhausting fossil oil products which release more exhaust. The aim of this research study is to decide the accessibility of biodiesel as an alternative fuel in diesel engines. In the current study, microalgae such as Diatom navicula sphaerophora green algae are used as the source for biodiesel production. The Diatom navicula sp. algae is a harvested biomass and its rate of growth doubles in one day. The Diatom navicula sp. algae can be selected for the biodiesel production. The chemical as well as physical properties of NAME [Naviculla algae methyl ester] blends with La2 O3 nano additives are determined and compared to fulfill the ASTM standards. In this work, blends of B20 with La2 O3 as the additive with different proportions have been used as fuel. The research was carried out on a single cylinder four stroke diesel engine, keeping a constant speed of 1500 rpm. Four blends are prepared by biodiesel as B20 along with three blends of diesel–biodiesel- La2 O3 using 50 ppm and 100 ppm concentrations of La2 O3 . The final results showed that B20 with La2 O3 additives is a best alternative fuel for the diesel engine to increase performance and reduce engine exhaust pollution levels.